1999
DOI: 10.1101/gad.13.23.3125
|View full text |Cite
|
Sign up to set email alerts
|

Compartmentalized signaling by GPI-anchored ephrin-A5 requires the Fyn tyrosine kinase to regulate cellular adhesion

Abstract: Eph receptor tyrosine kinases and their corresponding surface-bound ligands, the ephrins, provide cues to the migration of cells and growth cones during embryonic development. Here we show that ephrin-A5, which is attached to the outer leaflet of the plasma membrane by a glycosyl-phosphatidylinositol-anchor, induces compartmentalized signaling within a caveolae-like membrane microdomain when bound to the extracellular domain of its cognate Eph receptor. The physiological response induced by this signaling even… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
207
1

Year Published

1999
1999
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 273 publications
(214 citation statements)
references
References 64 publications
6
207
1
Order By: Relevance
“…Whereas complementary expression of ephrins and Eph receptors results in spatial segregation of receptor-bearing cells from ligand-bearing cells Xu et al, 1999), the functional consequences of coexpression of ephrins and Eph receptors are unknown. Because overlapping expression patterns allow for extensive interactions, binding of ephrin-A1 to EphA2 in tumor tissue could lead to activation of signaling pathways downstream of EphA2 and possibly ephrin-A1 (Kalo and Pasquale, 1999;van der Geer et al, 1994;Dodelet and Pasquale, 2000;Davy et al, 1999). Consistent with this hypothesis, we found that EphA2 is phosphorylated on tyrosine in the tumor xenografts.…”
Section: Discussionsupporting
confidence: 73%
“…Whereas complementary expression of ephrins and Eph receptors results in spatial segregation of receptor-bearing cells from ligand-bearing cells Xu et al, 1999), the functional consequences of coexpression of ephrins and Eph receptors are unknown. Because overlapping expression patterns allow for extensive interactions, binding of ephrin-A1 to EphA2 in tumor tissue could lead to activation of signaling pathways downstream of EphA2 and possibly ephrin-A1 (Kalo and Pasquale, 1999;van der Geer et al, 1994;Dodelet and Pasquale, 2000;Davy et al, 1999). Consistent with this hypothesis, we found that EphA2 is phosphorylated on tyrosine in the tumor xenografts.…”
Section: Discussionsupporting
confidence: 73%
“…Glycosylphosphatidylinositol-anchored ephrinA5 can induce compartmentalized signaling within a membrane microdomain when bound to its cognate Eph receptor. This signaling seemed to require the activity of the Fyn protein tyrosine kinase (Davy et al, 1999). We showed that ephrinA5 colocalized with EGFR in certain regions on the plasma membrane.…”
Section: Discussionmentioning
confidence: 78%
“…Although ephrinA5 is a glycosylphosphatidylinositol-linked membrane protein, it is also able to elicit intracellular signaling transduction, such as activation of Src family kinases (Davy et al, 1999). We supposed that the ephrin reverse signaling also participated in the downregulation of EGFR, considering the presence of endogeneous EphA receptors for ephrinA5.…”
Section: Ephrina5-fc Treatment-induced Egfr Decrease and Sustained Egmentioning
confidence: 97%
“…It is possible that Nogo affects NgR multimerization in neurons that may possess additional components required for Nogo signaling. It is also possible that ligand binding modifies the localization of additional unidentified signaling components within the lipid raft, as is the case for ephrins (Davy et al, 1999). Because the components of the NgR intracellular signaling cascade have not been identified, the effect of Nogo on the recruitment of signaling components to lipid rafts remains an open question.…”
Section: Ngr Binds Ngrmentioning
confidence: 98%